SPIRITUAL INTELLIGENCE FROM THE SHARIAH PERSPECTIVE AND ITS IMPORTANCE IN THE MILITARY PROFESSION IN MALAYSIA - Raja Raziff Raja Shaharuddin; Daud Mohamed Salleh; Muhammad Syukri Haji Zahari; Elmi Baharudin; Zahimi Zainol Abidin (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
Spiritual intelligence is an essential facet of human development, especially in professions that demand strong moral and psychological resilience, such as the Malaysian Armed Forces (MAF). From the Shariah perspective, it embodies faith (iman), piety (taqwa), excellence (ihsan), and a deep connection with Allah SWT guiding thoughts, emotions, and behaviour. This study explores the concept of spiritual intelligence through the lens of Shariah and examines its role in shaping values and enhancing career competence among MAF personnel. Adopting a qualitative methodology, the study draws upon classical and contemporary Islamic sources through textual analysis and literature review. Findings suggest that spiritual intelligence, grounded in maqasid al-shariah, fosters sincerity, responsibility, and resilience. The study recommends integrating spiritual development as a core element in MAF training and human capital strategies.